Return to school after brain injury. Issue 2 (21st January 2004) - Hawley, C A; Ward, A B; Magnay, A R; Mychalkiw, W
Abstract : Aims: To examine return to school and classroom performance following traumatic brain injury (TBI). Methods: This cross-sectional study set in the community comprised a group of 67 school-age children with TBI (35 mild, 13 moderate, 19 severe) and 14 uninjured matched controls. Parents and children were interviewed and children assessed at a mean of 2 years post injury. Teachers reported on academic performance and educational needs. The main measures used were classroom performance, the Children's Memory Scale (CMS), the Wechsler Intelligence Scale for Children–third edition UK (WISC-III) and the Weschler Objective Reading Dimensions (WORD). Results: One third of teachers were unaware of the TBI. On return to school, special arrangements were made for 18 children (27%). Special educational needs were identified for 16 (24%), but only six children (9%) received specialist help. Two thirds of children with TBI had difficulties with school work, half had attention/concentration problems and 26 (39%) had memory problems. Compared to other pupils in the class, one third of children with TBI were performing below average. On the CMS, one third of the severe group were impaired/borderline for immediate and delayed recall of verbal material, and over one quarter were impaired/borderline for general memory. Children in the severe group had a mean full-scale IQ significantly lower than controls. Half the TBI group had a reading age ⩾1 year below their chronological age, one third were reading ⩾2 years below their chronological age. Conclusions: Schools rely on parents to inform them about a TBI, and rarely receive information on possible long-term sequelae. At hospital discharge, health professionals should provide schools with information about TBI and possible long-term impairments, so that children returning to school receive appropriate support.